Black ginger: Importance, cultivation and prospects for Mizoram - Lungmuana; Lalramhlimi, B.; Soni, Jeetendra Kumar; Doley, Sunil (Indian Horticulture, 2025)
Black ginger (Kaempferia parviflora) is an emerging crop, highly prized for its medicinal and industrial uses. It is a rich source of methoxy flavones which have huge potential for pharmaceutical uses such as anti-allergen, anti-cancer, antiinflammatory, and also enhance sexual performance. In Mizoram, it is locally used by chewing a small piece of fresh rhizome for the treatment of stomachache and dysentery. It is predominantly found in the Northeastern part of India and its cultivation is favoured by pleasant climate throughout the year. Black ginger is found scattered in forested areas under partial shade and cultivation is mainly done for domestic uses and not for commercial purpose. Despite its globally recognized importance, the crop remains underutilized. Two key factors contributing to this underutilization are limited scientific understanding of optimal cultivation methods and lack of suitable genotypes for commercial cultivation. In order to harness the full potential of this crop, the development and implementation of standardized cultivation protocols are imperative for its successful commercialization in the region. Furthermore, conducting surveys, collecting germplasm, and evaluating accessions are essential steps in identifying superior genotypes with desirable traits.